1983
DOI: 10.1002/ardp.19833161106
|View full text |Cite
|
Sign up to set email alerts
|

2‐Amino‐3‐hydroxy‐ 1‐thiochromone1)

Abstract: 3161832-Amino-3-hydroxy-1 -thiochromone 921 Synthese der Pyridinium-Verbindungen 2 0,2mol4 werden mit 0,2 mol3-Brompyridin (Merck-Schuchardt) in Olbad 1,5 h auf 363 K erhitzt. Die ubrigen Reaktionsbedingungen sind wie bei der Synthese von 1.Synthese der Pyridinium-Verbindungen 3 Es wurde 3-Chlorpyridin (Loba Chemie, Wien) verwendet. Die ubrigen Reaktionsbedingungen sind wie bei der Synthese von 1. Priifung der antibakteriellen WirkungDie MHK der Pyridiniumchloride wurde im Reihenverdunnungstest gegenuber 13 Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…When the substrates 10a , e , 11a , and 12a , d were treated only with a slight excess (1.2 equiv) of DMD, both 1 H NMR analysis of the reaction mixture (Table ) and the yields of isolated materials (Table ) revealed a high proportion of sulfone and considerable amounts of unreacted sulfide; the expected sulfoxides were found only as minor products. A literature survey indicated that the sulfones of 1-thiochromones and 1-thioflavones are readily available by oxidation with hot H 2 O 2 in acetic acid, 3b,,,, hot peracetic acid, hot monoperoxyphthalic acid, or with H 2 O 2 in trifluoroacetic acid at room temperature . All attempts to synthesize the corresponding sulfoxides by using less oxidant and/or milder conditions failed in that only mixtures of sulfide, sulfoxides, and sulfones were obtained. 3a,, Indeed, the pure 1-thiochromone 1-oxide ( 13a ) 41 and 1-thioflavone 1-oxide ( 15a ) 15 can only be prepared by dehydrobromination of the respective 3-bromo-1-thiochroman-4-one derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…When the substrates 10a , e , 11a , and 12a , d were treated only with a slight excess (1.2 equiv) of DMD, both 1 H NMR analysis of the reaction mixture (Table ) and the yields of isolated materials (Table ) revealed a high proportion of sulfone and considerable amounts of unreacted sulfide; the expected sulfoxides were found only as minor products. A literature survey indicated that the sulfones of 1-thiochromones and 1-thioflavones are readily available by oxidation with hot H 2 O 2 in acetic acid, 3b,,,, hot peracetic acid, hot monoperoxyphthalic acid, or with H 2 O 2 in trifluoroacetic acid at room temperature . All attempts to synthesize the corresponding sulfoxides by using less oxidant and/or milder conditions failed in that only mixtures of sulfide, sulfoxides, and sulfones were obtained. 3a,, Indeed, the pure 1-thiochromone 1-oxide ( 13a ) 41 and 1-thioflavone 1-oxide ( 15a ) 15 can only be prepared by dehydrobromination of the respective 3-bromo-1-thiochroman-4-one derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction of 4,7-dimethoxy-5-oxo-5H-furo[3,2-g]chromene-6-carbaldehyde 1 [8,15,16] with (1H-benzimidazol-2-yl)methanamine dihydrochloride (2) [17] was previously studied by using a catalytic amount of triethyl amine or piperidine to give The side chains of the residues forming the catalytic triad (His-57, Asp-81, and Ser-139) are shown in red. The NS4A cofactor is shown in purple, the bound zinc ion is modeled in light green.…”
Section: Chemistrymentioning
confidence: 99%
“…Compared to the versatile synthetic methods leading to 2-aminobenzopyranone derivatives, the approaches to 2-aminobenzothiopyranones are somewhat limited. Some simple 2-aminobenzothiopyranones have been obtained by the cyclization of 2-thiobenzoylacetonitrile treated with a strong acid (method A, Scheme 1) [67], or through the reduction of 2-nitrobenzothiopyranones with sodium dithionite (method B, Scheme 1) [8]. Apparently, synthetic methods to afford N -substituted 2-aminobenzothiopyranones are less well developed.…”
Section: Introductionmentioning
confidence: 99%